By the Time You Read This : Stories - Murphy, Yannick (Book collections on Project MUSE., 2021)
"Yannick Murphy's By the Time You Read This is a collection of thirteen stories that presents characters whose simple lives reveal the fraught and contingent nature of their existence as they navigate disparate situations that readers will find at once both foreign and familiar"--